Supervisi Akademik Kepala Sekolah yang Humanis Dalam Meningkatkan Kinerja Guru - Warman, Warman; Hermansyah, Hermansyah; Kusmiati, Tati; Nurlelawati, Nurlelawati; Junainah, Junainah (UMSU, 2024)
This research aims to discuss humanistic academic supervision of school principals in fostering teacher professionalism. This paper was written using a literature review by choosing a narrative review model. The narrative review approach compares data from various journals that have been analyzed and summarized based on the author's experience, relevant theories and models. Analytical descriptive methods are used by collecting, identifying, compiling and analyzing various available data. The results of the research show that the use of humanistic academic supervision can improve teacher performance in carrying out tasks at school, and ultimately can improve student learning achievement.